Anemia in hospitalized patients: an overlooked risk in medical care - Krishnasivam, D.; Trentino, K.; Burrows, S.; Farmer, Shannon; Picardo, S.; Leahy, M.; Halder, A.; Chamberlain, J.; Swain, S.; Muthucumarana, K.; Waterer, G. (Wiley-Blackwell, 2018)
© 2018 AABB BACKGROUND: This study investigated the association between nadir anemia and mortality and length of stay (LOS) in a general population of hospitalized patients. STUDY DESIGN AND METHODS: A retrospective cohort study of tertiary hospital admissions in Western Australia between July 2010 and June 2015. Outcome measures were in-hospital mortality and LOS. RESULTS: Of 80,765 inpatients, 45,675 (56.55%) had anemia during admission. Mild and moderate/severe anemia were independently associated with increased in-hospital mortality (odds ratio [OR] 1.5, 95% confidence interval [CI] 1.36-1.86, p = 0.001; OR 2.77, 95% CI 2.32-3.30, p < 0.001, respectively). Anemia was also associated with increased LOS, demonstrating a larger effect in emergency (mild anemia—incident rate ratio [IRR] 1.52, 95% CI 1.48-1.56, p < 0.001; moderate/severe anemia—IRR 2.18, 95% CI 2.11-2.26, p < 0.001) compared to elective admissions (mild anemia—IRR 1.30, 95% CI 1.21-1.41, p < 0.001; moderate/severe anemia—IRR 1.69, 95% CI 1.55-1.83, p < 0.001). LOS was longer in patients who developed anemia during admission compared to those who had anemia on admission (IRR 1.13, 95% CI 1.10-1.17, p < 0.001). Red cell transfusion was independently associated with 2.23 times higher odds of in-hospital mortality (95% CI 1.89-2.64, p < 0.001) and 1.31 times longer LOS (95% CI 1.25-1.37, p < 0.001). CONCLUSION: More than one-third of patients not anemic on admission developed anemia during admission. Even mild anemia is independently associated with increased mortality and LOS; however, transfusion to treat anemia is an independent and additive risk factor.